The non-specific lipid transfer protein McLTPII.9 of Mentha canadensis is involved in peltate glandular trichome density and volatile compound metabolism - Chen, Qiutong; Li, Li; Qi, Xiwu; Fang, Hailing; Yu, Xu; Bai, Yang; Chen, Zequn; Liu, Qun; Liu, Dongmei; Liang, Chengyuan (Frontiers in Plant Science, 2023)
Mentha canadensis L. is an important spice crop and medicinal herb with high economic value. The plant is covered with peltate glandular trichomes, which are responsible for the biosynthesis and secretion of volatile oils. Plant non-specific lipid transfer proteins (nsLTPs) belong to a complex multigenic family involved in various plant physiological processes. Here, we cloned and identified a non-specific lipid transfer protein gene (McLTPII.9) from M. canadensis, which may positively regulate peltate glandular trichome density and monoterpene metabolism. McLTPII.9 was expressed in most M. canadensis tissues. The GUS signal driven by the McLTPII.9 promoter in transgenic Nicotiana tabacum was observed in stems, leaves, and roots; it was also expressed in trichomes. McLTPII.9 was associated with the plasma membrane. Overexpression of McLTPII.9 in peppermint (Mentha piperita. L) significantly increased the peltate glandular trichome density and total volatile compound content compared with wild-type peppermint; it also altered the volatile oil composition. In McLTPII.9-overexpressing peppermint, the expression levels of several monoterpenoid synthase genes and glandular trichome development-related transcription factors—such as limonene synthase (LS), limonene-3-hydroxylase (L3OH), geranyl diphosphate synthase (GPPS), HD-ZIP3, and MIXTA—exhibited varying degrees of alteration. McLTPII.9 overexpression resulted in both a change in expression of genes for terpenoid biosynthetic pathways which corresponded with an altered terpenoid profile in OE plants. In addition, peltate glandular trichome density was altered in the OE plants as well as the expression of genes for transcription factors that were shown to be involved in trichome development in plants.